Odpowiedzi

2009-12-14T17:37:37+01:00
A) (m + n)(m-2)+(m-n)(m+1)=m²-2m+nm-2n
b) (3x - 2)(3x - 2y +1) -4x(2x - 3y +1)=9x²-6xy+3x-6x+4y-2-8x²+12xy-4x=x²+6xy-7x+4y-2
c) 3(m+1)(n-2) +2(n+1)(m-2)=3(mn-2m+n-2)+2(mn-2n+m-2)=3mn-6m+3n-6+2mn-4n+2m-4=5mn-4m+7n-10
d) x (x +1)(x+2) -x(x - 1)(x-2)=x(x²+2x+x+2)-x(x²-2x-x+2)=x³+2x²+x²+2x-x³+2x²+x²-2x=6x²
2009-12-14T17:46:09+01:00
A) m² - 2m + mn - 2n + m² + m - mn - n =
2m² - m - 3n

b) 9x² - 6xy + 3x - 6x + 4y - 2 - 8x² + 12xy - 4x=
x² + 6xy - 7x + 4y - 2
c) 3mn - 6m + 3n - 6 + 2mn - 4n + 2m - 4 =
5mn - 4m - n - 10
d) x³ + 2x² + x² + 2x - x³ + 2x² + x² -2x
wszystko się skróci